A SPATIOTEMPORAL MODEL PREDICTS THE DYNAMICS OF A BASKETBALL GAME - A. Shana; Alsaeedi, Riyadh (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2024)
Abstract—Our work as a spatiotemporal model predictive dynamic (STMPD) on a basketball game capable of high-level decision making . Our motivated and skilled experts solve complex decision-making problems at every time point during a game. The conditional intensity of a temporal point process can be learned based on a network, and the likelihood is maximised during training. A Fine-grained player locations started with the simplest case of modelling, where certain players tend to shoot the ball. They discretize the court into cells fine enough to capture all significant spatial variations in model for predicting dynamics in-game, e.g., shooting policy, passing, and who relies on Markov transition probabilities to propagate action through a possession. We propose a method for learning factored Markov decision problems . We use a method that captures the multi-modal behaviour of the players' truth ground and estimation trajectory Prediction is a method for predicting multimodal trajectory by learning a model that assigns probabilities through conducting temporal classification (resolution) (CTC) architectures by generalising away from actual time stamps to recreate the predicted trajectory. Our proposed method of contribution is as follows : i) The method is built on an LSTM-based architecture predicting multiple trajectories and our probabilities, and then we use training with a multimodal loss function when updating the best trajectories . ii) a discriminative learning method for automatically training models to predict near-term game events based on current game conditions . iii) learning factored Markov decision processes (FMDP) problems from domain exploration and expert assistance, ensuring convergence to near-optimal behaviour even after the agent has started to learn critical success factors. IV) An algorithm 1,2, detects changes in possession, pass, and shot players that have been incrementally learned for all components of FMDP, and algorithm 3, which guarantees convergence to near-optimal behaviour even when the agent begins unaware of factors critical to success. A group of players shooting probability to enhance a probabilistic matrix